On line Webinars During Time of COVID-19: Does it Increase the Clinical and Surgical Skills of Egyptian Ophthalmologists? - Elshimaa A Mateen Mossa; Tasneem Mohammad Ali; Alahmady Hammad (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Introduction: Since the appearance of COVID-19 pandemic by the end of 2019 and beginning of 2020 conferences, and events are canceled targeting the social distance to limit the spread and decrease the danger of the newly emerging virus webinars instead spread all over the world as an educational tool with no risk of communications. Purpose: to evaluate the efficacy of webinars in increasing the clinical and surgical skills of Egyptian ophthalmologists during the time of obligatory social distancing of COVID-19. Results: most of ophthalmologists in this survey consider the webinars is a good educational tool and hoping to progress after COVID-19 Pandemic. Most of them followed their topics of interest rather than the speaker or the organizing company and interested till the end due to the more comfortable situations. Conclusion: Webinars are readily available technology inexpensive, beneficial experience added to the clinical and surgical skills of Egyptian ophthalmologists who are hoping to be continued even after the COVID-19 pandemic time.